Development of a human tyrosinase activity inhibition assay using human melanoma cell lysate - Gengxuan Shi; Yunjiang Feng; Kathryn F. Tonissen (BioTechniques)
Tyrosinase (TYR) inhibitors are required to treat skin hyperpigmentation. Currently live cell-based TYR assays and mushroom TYR in vitro assays are the common methods used to screen for TYR inhibitors. However, these methods are either time consuming and expensive or are not human TYR (hsTYR) specific. Here, we describe a simple hsTYR assay using cell lysate prepared from pigmented human melanoma cell lines that takes less than 3 hours to complete after collecting cell pellets. We confirmed the assay is species specific by using a known hsTYR inhibitor, kojic acid, as a positive control, while arbutin, which inhibits mushroom TYR, but not hsTYR, was not effective. This assay is a simple method to confirm hsTYR inhibition before conducting follow-up studies in live biological models.